Nrf2 mediates the protective effect of edaravone after chlorpyrifos‐induced nervous system toxicity. Issue 5 (13th February 2019) - Shou, Limeng; Bei, Yun; Song, Ying; Wang, Libo; Ai, Liyao; Yan, Qinying; He, Wei
Abstract: We aim to confirm the impairment of chlorpyrifos (CPF) in PC12 cells, evaluate the protective effect of edaravone on CPF‐induced injury, and try to unravel its underlying mechanism perspective from Nrf2 signaling pathway. Viability of PC12 cells treated with CPF and edaravone (Ed) were evaluated by MTT assay. Cell apoptosis was observed by the Hoechst 33342 stain. The level of reactive oxygen species (ROS), the content of malondialdehyde (MDA), and the activity of superoxide dismutase (SOD) were detected to evaluate the oxidative stress injury. The expression of Nrf2 was detected by Western blot; profoundly, RNA interference was conducted to construct Nrf2 gene knockdown PC12 cells and to uncover its underlying mechanism. MTT results showed CPF injured PC12 cells in a concentration‐dependent manner. Increased ROS and MDA content, decreased total SOD activity, or even apoptosis were occurred in PC12 cells when treated with CPF. Interestingly, CPF‐induced cell injury was conspicuously reversed after Ed administration. Nrf2 signaling pathway was activated after Ed treatment and the neuroprotective effect of Ed was not significant in cells after Nrf2 gene knockdown. In conclusion, Ed exerts neuroprotective effect on CPF‐induced oxidative stress injury and its mechanism was correlated with the Nrf2 signaling pathway.